Persuasion Strategies of Health Short Videos for Refuting Rumors - CHEN Yijin, MAI Jingyun, JIANG Qianying (Nongye tushu qingbao xuekan, 2023)
[Purpose/Significance] As a new means of information dissemination, short videos have become a new favorite of some people in spreading rumors and refuting rumors due to their characteristics of visibility, convenience, and freedom of expression. It is of great significance to understand the content characteristics of health short videos in rumor refuting and improve their spreading effect. [Method/Process] This paper uses Python to conduct data mining, crawling the rumor refuting short videos related to the theme of COVID-19 epidemic prevention and control as samples, and the data set obtained includes the published articles and the original data, such as the number of forwards, and comments. Based on "logos", "ethos" and "pathos" in Aristotle's rhetoric theory, this paper codes the persuasion strategies of sample videos in combination with the coding standard table of 13 persuasion strategies under four categories. At the same time, it divides short videos into seven video elements under two categories and